2017
DOI: 10.1039/c7lc00785j
|View full text |Cite
|
Sign up to set email alerts
|

Anisotropic permeability in deterministic lateral displacement arrays

Abstract: We uncover anisotropic permeability in microfluidic deterministic lateral displacement (DLD) arrays. A DLD array can achieve high-resolution bimodal size-based separation of microparticles, including bioparticles, such as cells. For an application with a given separation size, correct device operation requires that the flow remains at a fixed angle to the obstacle array. We demonstrate via experiments and lattice-Boltzmann simulations that subtle array design features cause anisotropic permeability. Anisotropi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
57
2

Year Published

2017
2017
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 45 publications
(59 citation statements)
references
References 33 publications
(37 reference statements)
0
57
2
Order By: Relevance
“…However, this DLD model of binary separation is incomplete due to the existence of the intermediate displacement mode of separation. This intermediate displacement mode is caused by the uneven pressure between the lateral and downstream direction that disrupts the flow streamline, which is called as the anisotropic permeability effect [20,[26][27][28][29].…”
Section: Dld Critical Diameter Modelmentioning
confidence: 99%
“…However, this DLD model of binary separation is incomplete due to the existence of the intermediate displacement mode of separation. This intermediate displacement mode is caused by the uneven pressure between the lateral and downstream direction that disrupts the flow streamline, which is called as the anisotropic permeability effect [20,[26][27][28][29].…”
Section: Dld Critical Diameter Modelmentioning
confidence: 99%
“…When obstacles sizes do not satisfy this condition, the hydrodynamics of the system cannot be disregarded and can significantly alter the observed phenomena in comparison to our model. These sources of discrepancies include the development of lateral pressure gradients as described by [12], edge effects at the interface between different chained lattices, and differences in particle advection trajectories post-collision due to the now non-trivial flow perturbation induced by the obstacles. However, work by Risbud & Drazer [5] [8] has identified that in systems with arbitrary obstacle sizes relative to the colloidal particles, the interaction dynamics between particles and obstacles are essentially identical to those described in Section II B except that the "output" displacements are ±b c , a parameter depending on the hydrodynamics of the microdevice and the particle/obstacle sizes, rather than ±r.…”
Section: Discussionmentioning
confidence: 99%
“…Having described a mathematical framework for understanding the collision frequencies and lateral displacements per length of particles advecting through chained obstacle lattices, we now discuss how we can use "chained" obstacle lattices to solve the inverse design problem of approximating a desired size-dependent lateral displacement or collision frequency function. For the purposes of the following analyses, we will focus specifically on the rotated square lattices described in Section 2.1.1 and Section 2.5.1, as this family of lattices exhibits isotropic fluid permeability (see [12]) which minimizes performance degradation due to induced lateral pressure gradients.…”
Section: A Approximating Displacement and Collision Functions Of Partimentioning
confidence: 99%
“…We found out that if we just remove those pillars, the empty spaces result in less hydraulic resistance and hence induces a lateral pressure gradient. This breaks the homogeneity of the flow and introduces significant errors in the cell trajectories [35,58]. Therefore, we decided to replace the circular pillars crossing the walls with elliptical pillars in such a way that they maintain the same vertical spacing with the neighboring pillars.…”
Section: Dld Modelmentioning
confidence: 99%